(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the psychological and pedagogical aspects of using game-based methods for teaching English as a second language. It provides an in-depth analysis of the literature related to game-based teaching, outlines various methods and approaches, discusses the results and their implications, and concludes with recommendations for educators looking to integrate games into their language teaching curriculum.